2013
DOI: 10.1136/bcr-2012-007874
|View full text |Cite
|
Sign up to set email alerts
|

Oral capillary haemangioma mimicking pyogenic granuloma: a challenge for diagnosis and management

Abstract: Pyogenic granuloma (PG) is a localised granulation tissue overgrowth, in reaction to mild irritation. The aetiology of the lesion is not known, though it was originally believed to be a botryomycotic infection. The clinical diagnosis of such a lesion can be quite challenging. The purpose of this article is to report an unusual case of benign tumour in an adolescent boy who was clinically diagnosed as PG and histopathologically as capillary haemangioma. PG being a benign lesion; surgical excision was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
3
0
4
Order By: Relevance
“…HEM, particularly the capillary type, should be differentiated from other vascular tumors, particularly from the pyogenic granuloma (PG; also called lobular capillary hemangioma). Histopathologically, both lesions resemble each other however PG is usually much smaller and more reactive in nature than HEM, it appears mostly in the gingiva, after the first year of life, and has a typical history of a non-healing/bleeding wound (23,34); furthermore, unlike HEM, PG is predominantly an epithelial rather than an endothelial lesion, and exhibits immunocytochemical and ultrastructural differences in relation to HEM. Although HEM and arteriovenous malformations (AVM) are considered clinically similar, both lesions exhibit some different histochemical and microscopic characteristics, which can help establish a definitive diagnosis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…HEM, particularly the capillary type, should be differentiated from other vascular tumors, particularly from the pyogenic granuloma (PG; also called lobular capillary hemangioma). Histopathologically, both lesions resemble each other however PG is usually much smaller and more reactive in nature than HEM, it appears mostly in the gingiva, after the first year of life, and has a typical history of a non-healing/bleeding wound (23,34); furthermore, unlike HEM, PG is predominantly an epithelial rather than an endothelial lesion, and exhibits immunocytochemical and ultrastructural differences in relation to HEM. Although HEM and arteriovenous malformations (AVM) are considered clinically similar, both lesions exhibit some different histochemical and microscopic characteristics, which can help establish a definitive diagnosis.…”
Section: Discussionmentioning
confidence: 93%
“…Histopathologic/microscopic features. In the present scoping review, seven articles (7,12,26,27,34,37,38) were identified in which a histopathological or microscopic evaluation was performed; all of them were clinical cases on pediatric oral HEM, particularly the capillary type. According to different authors (4,23,37), HEMs may present a spectrum of histopathological findings, consisting in general of hyperplastic endothelial cells exhibiting increased mitotic activity (13).…”
Section: Discussionmentioning
confidence: 99%
“…Os hemangiomas representam cerca de 7% de todos os tumores benignos, acometendo principalmente os membros, bexiga, área genital e sistema nervoso central (DA SILVA et al, 2014). Dentre aqueles que afetam a região de cabeça e pescoço, 14% acometem a cavidade oral (GOLDBLUM; FOLPE; WEISS, 2020), podendo ocorrer em língua, lábios, mucosa jugal, gengiva, palato, glândulas salivares, rebordo alveolar e ossos da mandíbula (PATIL et al, 2013).…”
Section: Discussionunclassified
“…A etiologia do hemangioma ainda não está bem elucidada, entretanto teorias de que a lesão pode se desenvolver a partir de células progenitoras endoteliais intrínsecas ou de angioblastos de origem placentária são suportadas (DARROW et al, 2015). O hemangioma infantil apresenta predileção pelo gênero feminino (DARROW et al, 2015;PATIL et al, 2013).…”
Section: Discussionunclassified
“…4,8 In the present case, poor oral hygiene (dental calculus) and irregular margins of the metal-ceramic crowns were the major predisposing factors. Differential diagnosis mainly includes vascular tumors like haemangioma, 9 oral fibroma, 10 peripheral giant cell granuloma, peripheral ossifying fibroma 11,12 or neoplastic lesions like Kaposi sarcoma, 13 metastatic carcinoma and other malignant tumors. 14,15 Drug induced gingival enlargement is sometimes noticed in Nifidepine users.…”
Section: Discussionmentioning
confidence: 99%